2023
DOI: 10.7759/cureus.34173
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Role of Biomarkers in COVID-19 Mortality

Abstract: BackgroundThe coronavirus disease 2019 (COVID-19) pandemic has resulted in high mortality among patients in critical intensive care units. Hence, identifying mortality markers in the follow-up and treatment of these patients is essential. This study aimed to evaluate the relationships between mortality rates in patients with COVID-19 and the neutrophil/lymphocyte ratio (NLR), derived NLR (dNLR), platelet/lymphocyte ratio (PLR), monocyte/lymphocyte ratio (MLR), systemic inflammation response index (SII), and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…However, the SII was capable of predicting mortality, but with lesser sensitivity and specificity as compared to the NLR. Such findings confirm the previous work of Ghobadi and his team [34], Gutiérrez-Pérez and colleagues [35] and Yılmaz and her team [36], as well as in Turkey [37]. In contrast, previous studies either refuted and excluded the value of the SII in the context of COVID-19 [38] or found it to be exclusively useful and to surpass the limited value of the NLR [32].…”
Section: Discussionsupporting
confidence: 88%
“…However, the SII was capable of predicting mortality, but with lesser sensitivity and specificity as compared to the NLR. Such findings confirm the previous work of Ghobadi and his team [34], Gutiérrez-Pérez and colleagues [35] and Yılmaz and her team [36], as well as in Turkey [37]. In contrast, previous studies either refuted and excluded the value of the SII in the context of COVID-19 [38] or found it to be exclusively useful and to surpass the limited value of the NLR [32].…”
Section: Discussionsupporting
confidence: 88%
“…The study design was prospective in three studies ( 50 , 67 , 68 ), unclear in one ( 66 ), and retrospective in the remaining 36 ( 21 , 36 49 , 51 65 , 69 74 ). The clinical endpoints included mortality in 19 studies ( 36 , 37 , 39 , 41 , 43 , 45 , 48 , 49 , 51 , 52 , 55 , 56 , 58 , 60 , 61 , 65 , 66 , 68 , 73 ), and measures of severe disease as follows: disease severity based on existing guidelines in eight ( 42 , 44 , 63 , 64 , 67 , 70 , 72 , 74 ), transfer to the intensive care unit (ICU) in eight ( 38 , 40 , 45 , 50 , 53 , 62 , 68 , 69 ), invasive mechanical ventilation in two ( 46 , 52 ), disease progression in two ( 57 , 71 ), prolonged hospital stay in one ( 21 ), intubation in one ( 37 ), deep vein thrombosis in one ( 54 ), acute pulmonary embolism in one ( 54 ), and acute limb ischemia in one ( 39 ). All studies reported the SII on hospital admission.…”
Section: Resultsmentioning
confidence: 99%
“…dNLR incorporates the total number of WBC into its calculation, making it a potentially more comprehensive indicator of infammation compared to NLR [16]. In infammatory diseases such as COVID-19, dNLR can not only refect the severity of the disease but also predict mortality of the disease [16], and dNLR displays a better predictive performance than NLR in prognosis of COVID-19 infected patients [20,21]. Our research fndings suggest that dNLR can also be an indicator of occult PsA, and this single factor has an extremely high sensitivity of 95.5%.…”
Section: Discussionmentioning
confidence: 99%